2023
DOI: 10.1002/adbi.202200158
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Lymphatic Vasculature in Fibrosis: Understanding the Biology to Improve the Modeling

Abstract: Fibrosis occurs in many chronic diseases with lymphatic vascular insufficiency (e.g., kidney disease, tumors, and lymphedema). New lymphatic capillary growth can be triggered by fibrosis‐related tissue stiffening and soluble factors, but questions remain for how related biomechanical, biophysical, and biochemical cues affect lymphatic vascular growth and function. The current preclinical standard for studying lymphatics is animal modeling, but in vitro and in vivo outcomes often do not align. In vitro models c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 153 publications
(463 reference statements)
0
1
0
Order By: Relevance
“…Mechanical cues are important in regulating the function of endothelial cells during vascular and lymphatic development. Dynamic mechanical properties, such as the shear stress induced by fluid flow, have inspired the design of dynamic hydrogels for engineering vascular and lymphatic tissues. ECM with softer mechanics has been shown to enhance lymphatic vessel formation by inducing a globin transcription factor binding protein 2 (GATA2) dependent transcriptional program . We previously showed a covalently cross-linked HA hydrogel with matrix stiffness priming lymphatic CLS formation directed by vascular endothelial growth factor-C (VEGF-C) .…”
Section: Resultsmentioning
confidence: 99%
“…Mechanical cues are important in regulating the function of endothelial cells during vascular and lymphatic development. Dynamic mechanical properties, such as the shear stress induced by fluid flow, have inspired the design of dynamic hydrogels for engineering vascular and lymphatic tissues. ECM with softer mechanics has been shown to enhance lymphatic vessel formation by inducing a globin transcription factor binding protein 2 (GATA2) dependent transcriptional program . We previously showed a covalently cross-linked HA hydrogel with matrix stiffness priming lymphatic CLS formation directed by vascular endothelial growth factor-C (VEGF-C) .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been increased focus on the relationship between tissues stiffness and lymphatic vessel response, primarily with lymphatic capillaries and LECs [6][7][8]. For our study, we focused on tissue stiffness levels that are found in fibrotic disease conditions, since tissue stiffening from excess ECM deposition and crosslinking are major features of fibrosis that alter the biophysical and biochemical microenvironments surrounding lymphatic vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In many of these healing and disease states, the tissue surrounding lymphatic vasculature undergoes dynamic biochemical (e.g., soluble factors) and biophysical (e.g., stiffness) changes that influence cell behavior [2][3][4][5]. One important biophysical change is increased tissue stiffening that is often associated with chronic fibrosis-a pathological wound healing condition marked by excess tissue deposition and scarring [6]. Increased tissue deposition and subsequent tissue densification also alters tissue transport properties, which changes the biochemical environment by altering how signaling molecules move through the tissue to reach cells.…”
Section: Introductionmentioning
confidence: 99%